Drought and heat stress on cotton genotypes suggested agro-physiological and biochemical features for climate resilience - Zafar, Muhammad Mubashar; Chattha, Waqas Shafqat; Khan, Azeem Iqbal; Zafar, Saba; Subhan, Mishal; Saleem, Huma; Ali, Arfan; Ijaz, Aqsa; Anwar, Zunaira; Qiao, Fei; Shakeel, Amir; Seleiman, Mahmoud F.; et al. (Frontiers in Plant Science, 2023)
This study aimed to investigate the impact of individual drought, heat, and combined drought and heat stress on twelve cotton genotypes, including eight tolerant and four susceptible genotypes. A field experiment was carried out by employing a randomized complete block split-plot design, with treatments (control, drought, heat, drought + heat), and cotton genotypes assigned to the main plots and sub-plots respectively. The results showed that the combined stress had a more severe impact on the yield and fiber quality of cotton genotypes compared to individual stresses. Among the studied genotypes, FB-Shaheen, FH-207, MNH-886, and White Gold exhibited superior performance in regard to agronomic and fiber quality characters under combined stress environments. Physiological parameters, including transpiration rate, stomatal conductance, relative water contents, and photosynthetic rate, were significantly reduced under combined stress. However, specific genotypes, MNH-886, FH-207, White Gold, and FB-Shaheen, demonstrated better maintenance of these parameters, indicating their enhanced tolerance to the combined stress. Furthermore, the accumulation of reactive oxygen species was more pronounced under combined stress compared to individual stressors. Tolerant genotypes showed lower levels of H2O2 and MDA accumulation, while susceptible genotypes exhibited higher levels of oxidative damage. Antioxidant enzyme activities, such as superoxide dismutase, peroxidase, and catalase, increased under combined stress, with tolerant genotypes displaying higher enzyme activities. Conversely, susceptible genotypes (AA-703, KZ 191, IR-6, and S-15) demonstrated lower increases in enzymatic activities under combined stress conditions. Biochemical traits, including proline, total phenolic content, flavonoids, and ascorbic acid, exhibited higher levels in resistant genotypes under combined stress, while sensitive genotypes displayed decreased levels of these traits. Additionally, chlorophyll a & b, and carotenoid levels were notably decreased under combined stress, with tolerant genotypes experiencing a lesser decrease compared to susceptible genotypes.